A review of the development of In-Hospital Neutron Irradiator-1 and boron neutron capture therapy clinical research on malignant melanoma - Zhang, Zizhu; Liu, Tong (Therapeutic Radiology and Oncology, 2018)
Boron neutron capture therapy (BNCT) is a binary targeting radiation therapeutic modality. Neutron source is one of the basic conditions of BNCT research. Specially designed neutron source, which could be set in hospital, is needed urgently for doctors and researchers. China research group has developed In-Hospital Neutron Irradiator-1 (IHNI-1), which is a specially designed reactor-based neutron source for BNCT with thermal power 30 kW and suitable for hospital siting. IHNI-1 has highly efficient neutron beams for both shallow and deep tumor irradiation and has the features of inherent safety, low power, small size, long-time stable, easy and quick operation, environment-friendly and low investment for construction and maintain. This paper gives a review of the development of IHNI-1, including the structure introduction and main test operation result, characterization neutron beams and finally reviews on the first BNCT clinical research at IHNI-1.